2005
DOI: 10.1093/rheumatology/keh642
|View full text |Cite
|
Sign up to set email alerts
|

A regional audit of the use of COX-2 selective non-steroidal anti-inflammatory drugs (NSAIDs) in rheumatology clinics in the West Midlands, in relation to NICE guidelines

Abstract: Ninety-two per cent of patients attending rheumatology clinics who were taking NSNSAIDs should have been prescribed a COX-2-selective agent in relation to NICE guidance. Duration of use and age > or =65 yr emerged numerically as the most important risk factors. Significant numbers of patients taking NSNSAIDs may be at risk from adverse gastrointestinal events and clinicians may wish to review their prescribing patterns. Conversely, 97% of patients taking COX-2 agents were treated appropriately. Although practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…On this basis, many patients with RA and OA would qualify for COX-2 selective agents from the outset. 47 The risk at a particular time point appears similar, regardless of the duration of prior NSAID use, 41 but cumulative risk is likely to be greater with longer use. Some studies have indicated a higher risk of complications earlier during treatment 48 and the Celecoxib Long-term Arthritis Safety Study (CLASS) showed that GI events were rare with diclofenac after 3 months of treatment but continued to accrue with celecoxib.…”
Section: 45mentioning
confidence: 99%
“…On this basis, many patients with RA and OA would qualify for COX-2 selective agents from the outset. 47 The risk at a particular time point appears similar, regardless of the duration of prior NSAID use, 41 but cumulative risk is likely to be greater with longer use. Some studies have indicated a higher risk of complications earlier during treatment 48 and the Celecoxib Long-term Arthritis Safety Study (CLASS) showed that GI events were rare with diclofenac after 3 months of treatment but continued to accrue with celecoxib.…”
Section: 45mentioning
confidence: 99%
“…[11][12][13][14] Other regions and medical specialties may consider adopting such a model that also provides an excellent training opportunity for SpRs. Combining different methodological approaches may improve the quality of the audit process; this audit experience has been shared with ARMA and hopefully facilitated the development and publication of ARMA audit tools.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting data from a number of departments facilitates assessment of relatively large numbers of patients, allows comparison between departments, and acts as a training opportunity for planning, undertaking, analysing, presenting and publishing quality audits. [11][12][13][14] Using this methodology, the study aimed to assess the accessibility and quality of secondary care rheumatology services for patients with IA regionally using relevant ARMA standards of care as audit tools.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid-induced-osteoporosis NOS steroid audit 10 1,766 prophylaxis guidance (1998) 9 National Institute for Clinical Excellence. Non-steroidal anti-inflammatory/ COX 2 audit 18* 2,846 Cox-2 inhibitor guidance (2001) 10 British Society for Rheumatology (BSR). Anti-TNF ␣ guidance (2001) 11 Anti-TNF audit 12 1,441…”
Section: Abbreviated Titlementioning
confidence: 99%
“…Each involved approximately 2,000 patients across 10 to 13 units (Table 1). [9][10][11][12][13][14] The authors previously conducted a qualitative study with a small sample of healthcare professionals to evaluate this innovative regional audit programme. Findings from this work suggest that regional audit has specific strengths in the clinical governance armamentarium.…”
Section: Introductionmentioning
confidence: 99%